A new framework for simulation of heat treatments. (21st December 2010) - Simsir, Caner; Gur, C. Hakan
In this study, a mathematical framework based on finite element method (FEM) capable of predicting temperature history, evolution of phases and internal stresses during thermal treatment of metals and alloys was developed. The model was integrated into the commercial FEA software MSC.Marc® by user subroutines. The accuracy of the model was verified by simulating the quenching of eccentrically drilled steel cylinders. Simulation results were justified via SEM observations and XRD residual stress measurements.